The Modernization and Formation of Urban Malay Families: (Pemodenan dan Pembentukan Keluarga Melayu di Bandar) (Melayu: Jurnal Antarabangsa Dunia Melayu, 2016)
This study will evaluate the suitability of the family modernization theory (a combination of evolutionary and functional theory) for studying urban Malay communities in Malaysia, in terms of spousal selection, marriageable age, age difference between spouses, and family formation. Library research and field work were both used in this study. The study focused on a 17-storey block of flats in Kampung Kerinchi, Kuala Lumpur. The primary data in this study was obtained through surveys and interviews conducted with 47 low-income Malay families residing in this block of flats. Although the study shows that the formation of families replicates that of the Western model, and similarly has expoerienced sudden changes as a result of industrialization and urbanization, the handed-down roles and influence of the values and norms of traditional Malay society are still upheld by urban Malays.Keywords: family modernization theory, urbanization and industrialization, Malay family formation, change